Working parameters affecting earth-air heat exchanger (EAHE) system performance for passive cooling: A review - D Darius; Mohd Suffian Misaran@Misran; Md. Mizanur Rahman; Mohd Azlan Ismail; Adriana Erica Amaludin (2017)
The study on the effect of the working parameters such as pipe material, pipe length, pipe diameter, depth of burial of the pipe, air flow rate and different types of soils on the thermal performance of earth-air heat exchanger (EAHE) systems is very crucial to ensure that thermal comfort can be achieved. In the past decade, researchers have performed studies to develop numerical models for analysis of EAHE systems. Until recently, two-dimensional models replaced the numerical models in the 1990s and in recent times, more advanced analysis using three-dimensional models, specifically the Computational Fluid Dynamics (CFD) simulation in the analysis of EAHE system. This paper reviews previous models used to analyse the EAHE system and working parameters that affects the earth-air heat exchanger (EAHE) thermal performance as of February 2017. Recent findings on the parameters affecting EAHE performance are also presented and discussed. As a conclusion, with the advent of CFD methods, investigational work have geared up to modelling and simulation work as it saves time and cost. Comprehension of the EAHE working parameters and its effect on system performance is largely established. However, the study on type of soil and its characteristics on the performance of EAHEs systems are surprisingly barren. Therefore, future studies should focus on the effect of soil characteristics such as moisture content, density of soil, and type of soil on the thermal performance of EAHEs system.